Management of Epilepsy Issues in Women - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Management issues for women with epilepsy (WWE) are reviewed by a team of investigators in conjunction with the AAN Quality Standards Subcommittee.